The Relationship Between Leg Muscle Power, Arm Strength and Wrist Flexibility on Smash Accuracy for Volleyball Extracurricular Students at SMA 15 Bandar Lampung - Oktaviani Ananda Putri; Joan Siswoyo; Muhammad Fajril Rifaldo; Candra Kurniawan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the relationship between leg muscle power, arm strength and wrist flexibility on the Smash accuracy of male and female extracurricular volleyball students at SMA Negeri 15 Bandar Lampung. The method used in this research is quantitative correlational with a sample of 30 students, 15 male students and 15 female students. Data was collected through broad jump tests, push and pull dynamometer, goniometer, and position-based Smash tests. Data analysis was carried out using the Pearson correlation test, multiple correlation, as well as through the prerequisite tests for normality and linearity. The results of the multiple correlation test show that there is a strong relationship between leg muscle power, arm strength and wrist flexibility and smash accuracy for both male and female students. The results of the multiple correlation test show R = 0.740 for boys and R = 0.693 for girls, indicating a simultaneous relationship. The simultaneous contribution of these three variables to smash accuracy for male students was 55%, while for female students it was 48%, indicating a fairly strong contribution from the three variables to smash accuracy and significance (p<0.05).